Karakter Molekuler Gen AB- FAR 1 Nematoda Aphelenchoides besseyi Asal Lima Varietas Padi - Kurniawati, Fitrianingrum; Tondok, Efi Toding; Kusumah, Yayi Munara; Munif, Abdul (Jurnal Fitopatologi Indonesia, 2021)
Molecular Characters of AB-FAR Gene 1 of Aphelenchoides besseyi from Five Rice Varieties Aphelenchoides besseyi is known as nematode species that causes seed-transmitted white shoot disease in rice. One important gene that has been reported to control the pathogenicity of A. besseyi is AB FAR-1. The study was conducted to determine the character of the AB FAR-1 gene of A. besseyi extracted from rice seeds. Nematode extraction was carried out using Baerman funnel method from the seeds of 5 rice varieties, i.e. “Ciherang”, “Inpari Sidenuk”, “Sintanur”, “Prime Hybrid” and “Pak Tiwi”. Total DNA extraction of nematodes was conducted using CTAB method, followed by amplification of the AB FAR-1 gene using specific primers FAR-F1/R1 and nucleotide sequence analysis. Specific DNA band of AB FAR-1 gene measuring 150 bp was successfully amplified from all nematode samples. Sequence analysis showed that the AB FAR-1 gene had the highest homology (92.5 – 100%) with the Genbank accession no. JQ686690.1, which is the AB FAR-1 gene of A. besseyi from China. Despite having high homology, there were some nucleotide differences in the AB FAR-1 gene samples of A. besseyi from "Ciherang", "Inpari Sidenuk" and "Prime Hybrid". Further phylogenetic tree analysis differentiated the AB FAR-1 A. besseyi gene into 2 groups, i.e. group 1 consisting of the AB FAR-1 gene A. besseyi from China, "Sintanur", "Prime Hybrids" and "Pak Tiwi" and group 2 gene AB FAR-1 A. besseyi from "Ciherang", and "Inpari Sidenuk".